THE IMPACT OF TEAM-BASED LEARNING IN THE TEACHING CAMPUS PROGRAM ON STUDENT SELF-EFFICACY AND TEACHER PROFESSIONALISM - Tono Suwartono; Feisal Aziez; Lutfi Istikharoh; Miftahul Furqon; Shelia Anjarani; Saefurrohman Saefurrohman; Santhy Hawanti; Faisal Faisal (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2022)
This study aims to investigate the impact of team-based learning practice in the Teaching Campus program on the participating students' self-efficacy and the school mentor teachers' professionalism. A mixed methods approach was employed in this research. A total of 44 students (comprising 22 students who participated in the Teaching Campus program and 22 students who did not take the program) and seven teachers in partner schools were involved in the study. A questionnaire survey to assess students self-efficacy was administered. Interviews with teachers were also conducted to evaluate how much the program affected their professionalism during the activity. The responses obtained from questionnaires were analyzed using the inferential statistical tool of T-test, whereas the qualitative data elicited from interviews were analyzed using a thematic procedure. The ex-post facto design comparing self-efficacy of the two groups has shown that there is a significant difference, where the students who took part in the Teaching Campus program are  superior over those who did not. In addition, the teachers who co-worked with the students in their schools have stated that they benefited from the scheme. These results have strong implications for the 'Freedom to Learn - Freedom Campus' policy in current Indonesia's higher education system, more specifically the 'Teaching Campus' program, which includes team-based learning as an essential component. Betterment in its implementation is encouraged to make, according to results of this study.